PELATIHAN PEMBUATAN BONEKA JARI SEBAGAI MEDIA AJAR BAGI GURU TK KECAMATAN SERIRIT - Ni Nyoman Ari Ratnadi; Putu Agus Windu Yasa Bukian (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Formal education for children begins at an early age, 4 years old the early childhood education programs. Learning in Kindergarten is carried out using the principle of play because playing for children is a very enjoyable activity and is always carried out every day. Daily learning activities in Kindergarten to develop children's intelligence abilities are adapted to the learning principles and values developed in the prepared curriculum. The learning process in kindergarten schools uses facilities and infrastructure that support the achievement of educational goals. One of them is using learning media that is interesting to children. However, teachers have difficulty providing teaching media such as storytelling media as learning facilities, which is one of the obstacles faced by kindergarten teachers in Seririt District. This is caused by financial factors, lack of ideas, skills, and other equipment. Learning media does not have to be in the form of sophisticated digital technology, therefore researchers provide a training program for making finger puppets as a teaching medium to kindergarten teachers in the Seririt sub-district as service partners with the aim of helping teachers develop teaching media that can be used in the classroom. The implementation of this service lasted for three months. Methods for implementing this activity include drafting training guidelines, providing training on making finger puppets as a learning medium, and practicing direct teaching using the media that has been created. The results obtained during the implementation of this community service, namely through training in making finger puppets as a teaching medium, are able to increase the creativity of teachers in creating shapes and characters from the media they make and also develop an entrepreneurial spirit because the materials used can be found around us, thus making children become more enthusiastic in the learning process, and the class atmosphere becomes more enjoyable.